2019
DOI: 10.1371/journal.pgen.1008051
|View full text |Cite
|
Sign up to set email alerts
|

Anteroposterior patterning of the zebrafish ear through Fgf- and Hh-dependent regulation of hmx3a expression

Abstract: In the zebrafish, Fgf and Hh signalling assign anterior and posterior identity, respectively, to the poles of the developing ear. Mis-expression of fgf3 or inhibition of Hh signalling results in double-anterior ears, including ectopic expression of hmx3a . To understand how this double-anterior pattern is established, we characterised transcriptional responses in Fgf gain-of-signalling or Hh loss-of-signalling backgrounds. Mis-expression of fgf3 … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
23
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(25 citation statements)
references
References 55 publications
2
23
0
Order By: Relevance
“…Previous research has shown that Hmx2 and Hmx3 have crucial functions in ear development in mouse, and our recent work shows that this is also the case for Hmx3a in zebrafish ( Wang et al 1998 ; Wang et al 2001 ; Wang et al 2004 ; Wang and Lufkin 2005 ; Hartwell et al 2019 ). In mouse, both Hmx2 and Hmx3 mutants have ear defects and these are more severe in double mutants ( Wang et al 2001 ; Wang et al 2004 ).…”
supporting
confidence: 58%
See 4 more Smart Citations
“…Previous research has shown that Hmx2 and Hmx3 have crucial functions in ear development in mouse, and our recent work shows that this is also the case for Hmx3a in zebrafish ( Wang et al 1998 ; Wang et al 2001 ; Wang et al 2004 ; Wang and Lufkin 2005 ; Hartwell et al 2019 ). In mouse, both Hmx2 and Hmx3 mutants have ear defects and these are more severe in double mutants ( Wang et al 2001 ; Wang et al 2004 ).…”
supporting
confidence: 58%
“…The hmx3a SU3 allele was described previously ( Hartwell et al 2019 ). With the exception of hmx3a sa23054 (generated in the Zebrafish Mutation Project and obtained from the Zebrafish International Resource Centre), we created all of the other hmx2 , hmx3a , and hmx2;hmx3a double deletion mutants described in this paper using CRISPR mutagenesis.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations